Analisis Implementasi Kearsipan pada Kantor Desa Peguyangan Kangin - Marsya Pahlevy; Ni Nyoman Menuh; Ida Bagus Ngurah Wimpascima (Forum Manajemen, 2023)
The Peguyangan Kangin Village Office is one of the agencies that manages the operational activities of the village government. Administrative activities of the village office require archive management. The research objective was to find out how the analysis of the implementation of filings at the Peguyangan Kangin Village Office. Data collection techniques include: interviews with heads and staff of administrative and general affairs. Observation by making direct observations in the field to find out the actual conditions regarding the archives at the Peguyangan Kangin Village Office. The data analysis technique used is descriptive qualitative. The results of the research are that the creation of archives has been carried out well. Archives are stored in a special shelf so that they are easy to find, no special standards are applied. The obstacle is the lack of storage space in the village archive warehouse. The advice that can be given is to destroy archives for archives that have not been used for 5-6 years so that old archives do not accumulate in the village archive warehouse. For the destruction of archives, confirmation should be made at the Denpasar City Archives and Libraries Service regarding the archive destruction policy. The village office should digitize in managing archives so that archives stored can be easily searched.